2020
DOI: 10.1017/qrd.2020.9
|View full text |Cite
|
Sign up to set email alerts
|

A New Natural Defense Against Airborne Pathogens

Abstract: We propose the nasal administration of calcium-enriched physiological salts as a new hygienic intervention with possible therapeutic application as a response to the rapid and tenacious spread of COVID-19. We test the effectiveness of these salts against viral and bacterial pathogens in animals and humans. We find that aerosol administration of these salts to the airways diminishes the exhalation of the small particles that face masks fail to filter and, in the case of an influenza swine model, completely bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 35 publications
0
25
0
12
Order By: Relevance
“…Also, when compared with other gases (Air, O 2 , N 2 , and Argon), CO 2 gas has the highest inactivated viruses and bacteria rates in different NaCl solutions, even at ambient temperatures and normal atmospheric pressure (18). Recently, Edwards et al demonstrate the effectiveness of aerosol administration of nasal saline comprising calcium and sodium salts diminishes exhaled particles and acts as a new natural defense against airborne pathogens in the human airways (36). Moreover, Zare and his teamwork report that spraying micron-sized water droplets can act as an effective disinfectant by causing inactivation of over 98% of the bacteria.…”
Section: Universal Virucidal and Antimicrobial Activitymentioning
confidence: 99%
“…Also, when compared with other gases (Air, O 2 , N 2 , and Argon), CO 2 gas has the highest inactivated viruses and bacteria rates in different NaCl solutions, even at ambient temperatures and normal atmospheric pressure (18). Recently, Edwards et al demonstrate the effectiveness of aerosol administration of nasal saline comprising calcium and sodium salts diminishes exhaled particles and acts as a new natural defense against airborne pathogens in the human airways (36). Moreover, Zare and his teamwork report that spraying micron-sized water droplets can act as an effective disinfectant by causing inactivation of over 98% of the bacteria.…”
Section: Universal Virucidal and Antimicrobial Activitymentioning
confidence: 99%
“…These powerful air flows generate shear stress on the mucus surface, a thin layer of about 5-10 μm deep, generating tiny droplets, like sea mist. Pathogen picked back up into the air by the shedding of droplets of mucus and airway lining fluid can carry pathogen deeper into the lungs or back into the environment-potentially leading to pulmonary infection of the host and those in the vicinity of the host 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently 16 , we reported that a solution of calcium chloride and sodium chloride, with salinity similar to ocean salinity while with a particularly high-calcium chloride content, delivered to the airways of 10 human subjects with a mist of droplets possessing a diameter between 9 and 10 μm, suited to nasal and upper airway deposition, cleans the airways of exhaled aerosol particles, with particularly significant effect in those subjects who exhale the most particles.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, saline irrigation or aerosol may provide moisture, and as such, protect the airways. Saline may wet proteins, altering their functioning, contributing to a better quality of the ALF, its improved spreading, less bio-aerosol production, and -by its isotonic nature -it may also reverse bronchoconstriction, in case of hyper-secreted, potentially hypotonic ALF [16][17][18][19]31,37,38,61] Through these mechanisms, isotonic saline may aid to improve the oxygen passage and ventilation of the lungs during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently, it has been shown that saline inhibits replication of SARS-CoV-2 in vitro in Vero cells (see further point 3) [ [33]], while a study with nebulized neutral electrolyzed saline was found to reduce the qPCR positivity of the virus in 6 out of 10 subjects by day 4, in 80% by day 6 and in all of them by day 9 (for clinical results, see point 6) [ [34]]. Other studies of the effect of saline on bio-aerosols, listed in Table 1 [[35]-, [36], [37]], have generated similar results with other viruses or lung particles, con rming a reduction bio-aerosols.…”
Section: Wetting Properties Of Saline and Effect On Viral Spreading/tmentioning
confidence: 99%